Pendampingan Pengelolaan Kinerja Guru melalui Platform Merdeka Mengajar di SDN Sonraen - Netty E A Nawa; Maxsel Koro; Taty R Koroh; Martha K Kota; Jimylton Dethan; Fembriani Fembriani; Adam B N Benu; Gaudensius J Koten (Pakis Journal Institute, 2026)
Teacher performance management through the Merdeka Mengajar Platform (PMM) requires teachers to plan work-result targets, implement professional development activities, and upload evidence of performance in a documented manner. This community service article aims to describe the mentoring process for fulfilling teachers' Work Result Plans (RHK), strengthening school-based learning communities, and facilitating the upload of performance evidence at SDN Sonraen, Amarasi Selatan, Kupang Regency. The activity used a participatory mentoring method conducted in four sessions from October 2024 to January 2025. Data were collected through attendance records, observation notes, PMM access monitoring, documentation of community-of-practice activities, and recapitulation of teacher performance predicates. The mentoring stages included identification of PMM access, assistance in selecting RHK indicators, facilitation of learning-community activities, upload of performance evidence, and final evaluation. The results show that eight teachers fulfilled RHK requirements with a 100% achievement rate. Two teachers obtained the Excellent predicate and six teachers obtained the Good predicate. The learning community also produced good-practice sharing on teaching modules, clinical supervision, and coconut-based learning media. The program indicates that structured mentoring supported by principal leadership and collegial collaboration can improve teacher readiness in using digital performance-management systems.